2011
DOI: 10.1111/j.1524-4741.2011.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy of Breast Cancer with Pirarubicin Versus Epirubicin in Combination with Cyclophosphamide and 5-fluorouracil

Abstract: We performed a retrospective study of 856 breast cancer patients in our hospital, to compare the therapeutic effect of pirarubicin with cyclophosphamide and 5-fluorouracil (CPF) with the standard epirubicin-based regimen (CEF) in adjuvant treatment of breast cancer. Patients were given cyclophosphamide and 5-fluorouracil 500 mg/m(2) each, and either pirarubicin 40 mg/m(2) or epirubicin 75-100 mg/m(2) , every 3 weeks, six cycles. A total of 233 patients used CPF and 623 patients used CEF regimen. The clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…24 Moreover, THP and THP-based combination therapies are effective against various tumors without severe side effects in the clinic. [25][26][27][28] However, a previous study demonstrated that most of patients with cervical cancer were not sensitive to THP treatment. 5 An optimized dose of 60 mg of THP (approximately 180 ng/ml in blood) only has a 13.3% response rate in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, THP and THP-based combination therapies are effective against various tumors without severe side effects in the clinic. [25][26][27][28] However, a previous study demonstrated that most of patients with cervical cancer were not sensitive to THP treatment. 5 An optimized dose of 60 mg of THP (approximately 180 ng/ml in blood) only has a 13.3% response rate in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that THP partially overcomes the resistance caused by overexpression of P-gp and that THP may play an important role in treatment of patients with refractory or recurrent high-grade osteosarcoma. In fact, THP has also shown favorable activity in various types of cancer cells, including P-gp overexpressing breast cancer [27] , ADM-resistant lymphoblastoma [28] , MG-63 cells [29] and bladder cancers [30] in vitro, and has substantial clinical activity against various tumors without severe side effects [4][5][6][7]15,16] . Despite the ability of THP to overcome MDR in clinical studies [6,16,17] , very little is known about THP-induced cytotoxicity and the underlying mechanisms of pirarubicin on MDR osteosarcoma cells.…”
Section: Wwwnaturecom/aps Zheng Se Et Almentioning
confidence: 99%
“…Recently, pirarubicin (THP), a novel anthracycline derivative of ADM, has been used clinically to treat tumors such as osteosarcoma, breast cancer, lymphoma and acute myeloid leukemia [4][5][6][7] . Moreover, THP has shown a greater antitumor activity [8][9][10] and lower cardiotoxicity [11] than ADM.…”
Section: Introductionmentioning
confidence: 99%
“…Existing NACT protocols often include docetaxel, anthracycline, cyclophosphamide, and trastuzumab, which are effective in treatment of BC [21]. Notably, anthracyclines, such as pirarubicin (THP) and epirubicin (EPI), are standard combinations in NACT regimen in BC [22]. THP and EPI treatment correlates with significantly elevated disease-free and overall survival in BC [23].…”
Section: Introductionmentioning
confidence: 98%
“…THP has improved antitumor activity and lower acute cardiotoxicity, with a response rate of 23.2 % in advanced BC [24]. EPI is one of the most frequently used chemotherapy agents in BC treatment because of its fewer side effects, e.g., lower cardiac toxicity than doxorubicin or mitoxantrone [22]. The efficacy of combination therapy is generally better than single-agent chemotherapy in many aspects, including higher overall survival in BC patients [25].…”
Section: Introductionmentioning
confidence: 99%